Correlation between Knowledge and Personal Hygiene Behavior among Female Adolescents during Menstruation: A Study at MTSN Binanga School - Hastuty, Yulina Dwi; Nasution, Nur Atika; Rahmah, Lestari; Kumalasari, Kumalasari (Poltekkes Kemenkes Riau, 2023)
Personal hygiene during menstruation is behavior related to maintaining health and efforts to maintain the cleanliness of the female area during menstruation. Adolescents who do not apply methods of caring for their reproductive areas during menstruation cause reproductive health problems such as sexual transmitted disease, cervical cancer and other reproductive health problems. One of the factors that influence the personal hygiene behavior of young women during menstruation is knowledge. Knowledge about personal hygiene influences behavior in maintaining and caring for reproductive health during menstruation. This study aims to determine correlation between knowledge and personal hygiene behavior of female adolescents during menstruation at MTs N Binanga school in 2022. This type of research used quantitative research, analytic survey methods with a cross-sectional design. The sample was 86 students of class IX students of MTs N Binanga school and used purposive sampling technique. Data collection using a questionnaire. Data analysis used the chi-square test. The results showed that respondents had good knowledge and positive behavior (84%) and respondents who had less knowledge and negative behavior (57%). With a p-value = 0.002 <α = 0.05, which means there was a correlation between knowledge and personal hygiene behavior of young women during menstruation. The conclusion of this study was that there was correlation between knowledge and personal hygiene behavior of young women during menstruation at MTs N Binanga school. From these results, it is suggested to young women to perform good personal hygiene during menstruation.